(untitled) (Journal of Enam Medical College, 2019)
Introduction: Exercise tolerance test (ETT) is an established screening test for coronary artery disease (CAD), but not feasible in 30−40% of patients. Dobutamine stress echocardiography (DSE) is an excellent alternative. Traditionally, inducible worsening of wall motion by 1 grade from baseline provides an index of CAD; worsening by 2 grade or more theoretically represents a more severe perfusion abnormality. The present study represents the inaugural experience of DSE at the National Institute of Cardiovascular Disease, Dhaka. Objective: To assess the predictive accuracy of DSE results with the presence and extent of CAD in subjects with suspected stable angina pectoris. Materials and Methods: In this prospective observational study, 35 subjects with intermediate to high probability of CAD were subjected to DSE followed by coronary angiography (CAG) within one month. Comparison of DSE results and predicted coronary artery involvement with angiographic findings were done. Overall sensitivity, specificity, accuracy as well as accuracy by arterial territory involvement were calculated. Results: DSE identified 82 abnormal segments, 66 with 1 grade change in 23 subjects (Group A) and 16 with 2 grade change in 8 subjects (Group B). CAG detected 54 significant lesions, 23 (42.59%) in left circumflex (LCX), 18 (33.33%) in left anterior descending (LAD), 11 (20.37%) in right coronary (RCA) and 2 (3.7%) in left coronary (LCA) artery. DSE had a sensitivity of 93.1% and a specificity of 66.7%. The accuracy was 88.57% overall, 94.29% for LAD and 91.43% for both LCX and RCA territories. Group B subjects had significantly higher number of coronary stenosis per patient (2.63 versus 1.38, p<0.001), triple vessel (62.5% versus 8.6%, p=0.003) and lower single vessel CAD (0% versus 47.8%, p=0.005). Conclusion: This study shows that DSE is a reliable test for prediction of the presence and extent of CAD. J Enam Med Col 2019; 9(1): 16-24